Strategi Pengembangan Bisnis Melalui Pendekatan Business Model Canvas pada Usaha Craftwave.id - Mia Putri Yeza; Marsya Halya Alfrida; Fauzi Adi Saputra; Wien Kuntan (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research explores the application of the Business Model Canvas (BMC) approach to develop Craftwave.id, a digital service provider specializing in website creation and Instagram content management. The study employs a qualitative descriptive methodology, emphasizing a comprehensive analysis of nine key elements of the BMC framework, including customer segmentation, value propositions, and revenue streams. Findings reveal that by optimizing digital marketing channels and strategic partnerships, Craftwave.id can effectively expand its market reach and improve operational efficiency. The implications suggest the potential for increased revenue and sustained competitiveness in the evolving digital landscape.